GSK-3Beta-Dependent Activation of GEF-H1/ROCK Signaling Promotes LPS-Induced Lung Vascular Endothelial Barrier Dysfunction and Acute Lung Injury - Yi, Lei; Huang, Xiaoqin; Guo, Feng; Zhou, Zengding; Chang, Mengling; Huan, Jingning (Frontiers in Cellular and Infection Microbiology, 2017)
The bacterial endotoxin or lipopolysaccharide (LPS) leads to the extensive vascular endothelial cells (EC) injury under septic conditions. Guanine nucleotide exchange factor-H1 (GEF-H1)/ROCK signaling not only involved in LPS-induced overexpression of pro-inflammatory mediator in ECs but also implicated in LPS-induced endothelial hyper-permeability. However, the mechanisms behind LPS-induced GEF-H1/ROCK signaling activation in the progress of EC injury remain incompletely understood. GEF-H1 localized on microtubules (MT) and is suppressed in its MT-bound state. MT disassembly promotes GEF-H1 release from MT and stimulates downstream ROCK-specific GEF activity. Since glycogen synthase kinase (GSK-3beta) participates in regulating MT dynamics under pathologic conditions, we examined the pivotal roles for GSK-3beta in modulating LPS-induced activation of GEF-H1/ROCK, increase of vascular endothelial permeability and severity of acute lung injury (ALI). In this study, we found that LPS induced human pulmonary endothelial cell (HPMEC) monolayers disruption accompanied by increase in GSK-3beta activity, activation of GEF-H1/ROCK signaling and decrease in beta-catenin and ZO-1 expression. Inhibition of GSK-3beta reduced HPMEC monolayers hyper-permeability and GEF-H1/ROCK activity in response to LPS. GSK-3beta/GEF-H1/ROCK signaling is implicated in regulating the expression of beta-catenin and ZO-1. In vivo, GSK-3beta inhibition attenuated LPS-induced activation of GEF-H1/ROCK pathway, lung edema and subsequent ALI. These findings present a new mechanism of GSK-3beta-dependent exacerbation of lung micro-vascular hyper-permeability and escalation of ALI via activation of GEF-H1/ROCK signaling and disruption of intracellular junctional proteins under septic condition.